MeCP2 binding to DNA depends upon hydration at methyl-CpG. - Ho, K; McNae, I; Schmiedeberg, L; Klose, R; Bird, A; Walkinshaw, MD (2008)
MeCP2 is an essential transcriptional repressor that mediates gene silencing through binding to methylated DNA. Binding specificity has been thought to depend on hydrophobic interactions between cytosine methyl groups and a hydrophobic patch within the methyl-CpG-binding domain (MBD). X-ray analysis of a methylated DNA-MBD cocrystal reveals, however, that the methyl groups make contact with a predominantly hydrophilic surface that includes tightly bound water molecules. This suggests that MeCP2 recognizes hydration of the major groove of methylated DNA rather than cytosine methylation per se. The MeCP2-DNA complex also identifies a unique structural role for T158, the residue most commonly mutated in Rett syndrome.